Academies, autonomy, equality and democratic accountability: Reforming the fragmented publicly funded school system in England. (14th March 2019) - West, Anne; Wolfe, David
Abstract : This article focuses on the transformative academies policy in England. Based on an analysis of documentary evidence, we argue that the policy has resulted in the fragmentation of the state-funded school system and stark variation between academies, with those within multi-academy trusts (MATs) having no legal identity. We examine the variation between funding agreements, the control by central government, the role of MATs and the governance of academies. We propose policy options to improve the current incoherent and fragmented set of provisions, including restoring the legal identity of schools in MATs and allowing academies if they so wish, to convert to maintained schools.